Viabilidad de adaptar un modelo de negocio internacional en la promoción de negocios de consumo de café en Palmira. - Calvo Nagles, Edinson Steven; Valencia Cardona, Pedro Luis (Universidad Antonio Nariño, 2021)
It is essential to understand that coffee has become an important part of the lives of individuals living in modern societies. In this sense, the objective is to recognize the potential for adaptation of a model of international business, according to the consumer behavior of coffee in Palmira, taking into account the tastes and preferences of the demand identified in relation to the environment. Regarding the method, it should be noted that it was developed through a descriptive-deductive study, the data was collected through a survey of 313 people in the city of Palmira; This amount was deducted taking into account the total population of the city and removing the biases that were people under 15 years of age and those over 74. Compared to the results, it is evident that 34.82% of Palmirans do prefer to go to a cafeteria, where it is highlighted that 95.3% would prefer to find a cozy and innovative space to share around a Café, where the American environment was the most preferred with the European one and where the second consumption space is households, this being favorable option for isolation due to Covid -19, as an alternative to operate within what the current international situation may require.